Academic entrepreneurship: A focus on entrepreneurial alertness, attitudes, norms and beliefs - Urban, B. (South African Journal of Higher Education, 2019)
Considering the increasing importance of the “third mission” to universities, several scholars recognise that academic entrepreneurship is required for successful commercialisation of research and venture start-ups. While several universities in South Africa have embarked on establishing technology transfer offices, the potential effect of academic entrepreneurship has yet to be realised. This study aims to provide insights into how an individual’s entrepreneurial alertness shapes their attitudes, beliefs and norms in terms of academic entrepreneurship. Following a survey, the results show that “attitudes towards behaviour, subjective norms, and perceived behavioural control” are significantly increased when higher levels of entrepreneurial alertness are prevalent. Educators are encouraged to design curricula focused on improving entrepreneurial alertness by considering its antecedents in relation to academic entrepreneurship.